2024, A Landmark Year for Climate Change and Global Carbon Capture, Utilization, and Storage: Annual Progress Review - Shangli Shi; Yun Hang Hu (Energy Science & Engineering)
ABSTRACT This annual review outlines the progress of carbon capture, utilization, and storage (CCUS) technologies in 2024. As human‐induced CO2 emissions continued to rise, the year presented critical challenges. Notably, 2024 was the hottest year on record and the first in which global temperatures exceeded preindustrial levels by more than 1.5°C, driving intensified efforts to advance CCUS. Scientific interest in CCUS grew significantly, with the annual number of related publications increasing by 11.4% compared to 2023, reaching 53,970. The total number of operational commercial CCUS facilities also expanded, rising by 16.3% to a total of 50. In the political area, governments introduced targeted policies to accelerate CCUS adoption, focusing on economic investment and specific implementation requirements.